2017
DOI: 10.30699/ijp.2017.25647
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia as the Main Cause of Pancytopenia in Iranian Population

Abstract: Background & objective: Pancytopenia is the reduction in the number of all 3 major cellular elements of blood and leads to anemia, leukopenia, and thrombocytopenia. A wide variety of etiologies result in pancytopenia including leukemia, aplastic anemia, and megaloblastic anemia. The current study identified the different etiologies of pancytopenia based on bone marrow examination in Iranian patients with pancytopenia. Methods: A total of 683 cases of pancytopenia with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our patient with underlying leukemia was pancytopenia at the time of presentation. This finding was consistent with a study from Iran, that showed acute myeloid leukemia could manifest as pancytopenia, especially in adults 11 . Acute myelomonocytic leukemia accounts for 5-10% of AML cases.…”
Section: Discussionsupporting
confidence: 93%
“…Our patient with underlying leukemia was pancytopenia at the time of presentation. This finding was consistent with a study from Iran, that showed acute myeloid leukemia could manifest as pancytopenia, especially in adults 11 . Acute myelomonocytic leukemia accounts for 5-10% of AML cases.…”
Section: Discussionsupporting
confidence: 93%
“…This is comparable to the findings of studies in Turkey and Iran. 45 , 46 Globally, malignancies are not a more common cause of pancytopenia in older patients. In studies conducted in India, megaloblastic anaemia was found to be the most common cause of pancytopenia, with no noticeably higher frequency of malignancy among older people.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are comparable with other studies investigating the aetiology of pancytopenia. 6 , 7 , 14 , 15 , 16 , 21 , 45 , 46 …”
Section: Methodsmentioning
confidence: 99%
“…Pancytopenia, an unspecific laboratory finding present in several diseases, is characterized by a reduction in the number of red and white blood cells and platelets. [ 1 ] The etiology of pancytopenia is multifactorial, including aplastic anemia, megaloblastic anemia, leukemia,[ 2 ] splenomegaly, sepsis, lymphoma, multiple myeloma, myelodysplastic syndromes, alcoholic diseases, viral infection, autoimmune diseases, and endocrine diseases. [ 1 ] Immune dysregulation following allogeneic stem cell transplantation is another important cause of immune-mediated pancytopenia.…”
Section: Introductionmentioning
confidence: 99%